Safety and efficacy of a feed additive consisting of endo‐1,4‐β‐xylanase produced with Trichoderma reesei CBS 114044 (ECONASE® XT) for pigs for fattening, laying hens and minor poultry species (AB Enzymes Finland Oy) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Roberto Edoardo Villa; Giovanna Azimonti; Eleftherios Bonos; Henrik Christensen; Mojca Durjava; Birgit Dusemund; Ronette Gehring; Boet Glandorf; Maryline Kouba; Marta López‐Alonso; Francesca Marcon; et al. (EFSA Journal)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the safety and efficacy of a product containing endo‐1,4‐β‐xylanase (ECONASE® XT) as a zootechnical feed additive (digestibility enhancer) for pigs for fattening, laying hens and minor poultry species. ECONASE® XT is available in two liquid and three solid forms and is produced with a genetically modified strain of Trichoderma reesei (CBS 114044). The FEEDAP Panel concluded that the genetic modification of the production strain does not raise any safety concerns, and viable cells of the production strain and its DNA were not detected in the final products. The Panel also concluded that ECONASE® XT is safe for pigs for fattening, laying hens and minor poultry species at the proposed conditions of use. The use of the additive raises no safety concerns for the consumers of products derived from animals fed with the additive or for the environment. The liquid and solid forms of ECONASE® XT are non‐irritant to the skin, but only the liquid forms were confirmed as non‐irritant to the eyes and not dermal sensitisers. The Panel could not conclude on the irritation potential to the eyes and the dermal sensitisation potential for the solid forms. Due to the proteinaceous nature of the active substance, the additive is considered to be a respiratory sensitiser. The additive has the potential to be efficacious in pigs for fattening at 20,000 BXU/kg complete feed, in all laying poultry species at 12,000 BXU/kg complete feed and in minor poultry species other than laying birds at 8000 BXU/kg complete feed.